London - Dragicevich, Peter; Fallon, Steve;Filou, Emilie;Harper, Damian (Footscray, Victoria : Lonely Planet Publications, 2016)
Provides information on major points of interest, activities, accomodations, restaurants, shopping, transportation, and entertainment in the city of London.
Plan your trip -- Explore London -- Understand London -- Survival guide.
Includes index.
Keywords: GUIDEBOOKS